Immunological pathogenesis and treatment progress of adenovirus pneumonia in children - Yaowen Liang; Jie Wei; Jianjun Shen; Zihao Liang; Xiuchang Ma; Yuchen Du; Wenxian Qian; Hui Dong; Ping Huang; Apeng Chen; Changhua Yi (Italian Journal of Pediatrics)
Abstract Human adenovirus is an infectious agent that causes respiratory infections in adults and children. It has been found that immunocompromised children are highly susceptible to this pathogen, as it can swiftly evolve into severe pneumonia with multiple sequelae. Due to the lack of immunity in children, the body’s response mechanisms to innate and acquired immunity are specialized. We first examined the infection classification and clinical characteristics associated with adenovirus in children. Subsequently, we explored the in-depth understanding of the pathogenic mechanism of adenovirus pneumonia in children, focusing on immunological and cellular biological aspects. Adenovirus infection in children can disrupt the balance of the innate immune response, inducing immune cells to secrete an abundance of pro-inflammatory cytokines. This cascade results in a cytokine storm, which triggers an inflammatory response and causes lung tissue damage. As a result, the infection may progress to a severe state, potentially leading to multi-organ failure. Immunocompromised children exhibit impaired immune cell numbers and functions, which affects both the secretion of antibodies to humoral immunity and the immune response of cellular immunity to adenovirus. Lastly, we reviewed the progress in treating adenovirus pneumonia in children. There are many treatments for adenovirus pneumonia in children, which must be personalized based on a thorough assessment to optimize treatment outcomes. Recent advancements in pharmaceutical development have provided new treatment options for children. Immunomodulatory therapy can reduce inflammation in children, while adjuvant therapy can improve respiratory function; however, it can also lead to complications. Further, co-infections increased the complexity of diagnosis and treatment, necessitating dynamic adjustments to treatment regimens. This review could serve as the basis for identifying potential therapeutic approaches to alleviate the symptoms associated with adenovirus infections in children.